A Perspective on Reagent Diversity and Non-covalent Binding of Reactive Carbonyl Species (RCS) and Effector Reagents in Non-enzymatic Glycation (NEG): Mechanistic Considerations and Implications for Future Research - Rodnick, Kenneth J.; Holman, R. W.; Ropski, Pamela S.; Huang, Mingdong; Swislocki, Arthur L. M. (Frontiers in Chemistry, 2017)
This perspective focuses on illustrating the underappreciated connections between reactive carbonyl species (RCS), initial binding in the nonenzymatic glycation (NEG) process, and nonenzymatic covalent protein modification (here termed NECPM). While glucose is the central species involved in NEG, recent studies indicate that the initially-bound glucose species in the NEG of human hemoglobin (HbA) and human serum albumin (HSA) are non-RCS ring-closed isomers. The ring-opened glucose, an RCS structure that reacts in the NEG process, is most likely generated from previously-bound ring-closed isomers undergoing concerted acid/base reactions while bound to protein. The generation of the glucose RCS can involve concomitantly-bound physiological species (e.g., inorganic phosphate, water, etc.); here termed effector reagents. Extant NEG schemes do not account for these recent findings. In addition, effector reagent reactions with glucose in the serum and erythrocyte cytosol can generate RCS (e.g., glyoxal, glyceraldehyde, etc.). Recent research has shown that these RCS covalently modify proteins in vivo via NECPM mechanisms. A general scheme that reflects both the reagent and mechanistic diversity that can lead to NEG and NECPM is presented here. A perspective that accounts for the relationships between RCS, NEG, and NECPM can facilitate the understanding of site selectivity, may help explain overall glycation rates, and may have implications for the clinical assessment/control of diabetes mellitus. In view of this perspective, concentrations of ribose, fructose, Pi, bicarbonate, counter ions, and the resulting RCS generated within intracellular and extracellular compartments may be of importance and of clinical relevance. Future research is also proposed.